Access control for video-based collaborative learning frameworks - Blanco, Mae Sincere S.
Access control is becoming an admitted essential requirements in collaborative learning environments. However with the existing video-based collaborative learning frameworks, still the support for this feature receives less attention. This research aims to improve on these frameworks by introducing an access control mechanisms to the video annotations that will ensure organization and trustworthiness of their learning content and address potential privacy issues. Our approach introduces the use of discussion threads which provides different groups of users separate interfaces for their discussions. The use of discussion threads provides video repurposing and access control. Users reuse the videos for different purposes such that users could create variety of discussion threads for the given video. Also users could customize the privacy of their discussion threads. They may opt to make the discussion threads available only to specific users or they may opt to open it to the public wherein anyone could participate in their discussions. In order to evaluate the usefulness of the introduced feature, a working prototype is implemented and is evaluated in terms of its usability. Testers agreed to the usefulness and advantages of features for moderating discussion and on providing options to the privacy setting of the discussion threads. However, they also argued that the user interface (UI) of the system is not that user-friendly. Nevertheless, the system was reimplemented to resolve the problems discovered and to make it easier to use.